SHI’AH ABAD KESEPULUH (PERAN DINASTI BUWAIHIYYAH DALAM KEBANGKITAN INTELEKTUAL DAN KEBUDAYAAN ISLAM) - Hidayah, Fathi; Fadlullah, Muhammad Endy (FKDP (Forum Komunikasi Dosen Peneliti), 2020)
The discussion of Shi'ah has never been eaten in the days. There is still much debate about minority spin-off groups that have made a significant contribution to the development of the social, political and ekonimi history of Muslims. In some stages of the Shi'ah Dynasty, the Buwaihiyyah period had at least the largest share in the intellectual and cultural revival of Islam. There are several features in this time that can be used as indicators of the cultural and intellectual revival of society, especially the cultural elite, namely individualism, cosmopolitanism and secularism, all of which existed during the Buwaihiyyah Dynasty. Religious life during the Buwaihiyyah period tended to be conducive and peaceful although there were still frictions of interest between Sunnis and Shi'ah. Friction even occurred with sufi groups but the compromise approach that Buwaihiyyah seemed to make the constalation of interest competition less obvious. This condition does not mean that Shi'ah as the Buwaihiyyah dynasty did not develop, precisely the progress of Shi'ah culture and rituals developed very rapidly at this time, the ritual ceremony ghadir Khumm (commemorating the appointment of 'Ali as a prophet' ceremony) and the ceremony 'Ashura (commemorating the martyrdom of Husayn ibn 'Ali). Through the study of the library, this study took data from various references containing the history of Dinasati Buwaihiyyah. Data analysis uses technical content analysis to produce comprehensive data on the picture of the Buwaihiyyah dynasty in the tenth century.